Relación entre postura corporal ocupacional y grado de artrosis lumbar en pacientes mayores de 45 años de edad - Avalos Mendoza, Julisa Fiorella (2014)
Arthrosis is the most common form of arthropathy and a major cause of functional disability and reduction in the quality of life of older adults. Commonly considered as a disease of the peripheral joints, osteotrosis of the spine is often ignored in discussions about the prevalence and effect of osteoarthrosis on disability and function. Several studies show that the body postures adopted by people in their different occupational activities show some relationship with the damage caused in the lumbar spine. OBJECTIVE: To determine the existence of a relationship between occupational body posture and the degree of lumbar osteoarthritis in patients over 45 years of age with a diagnosis of lumbar osteoarthritis attended in the external rheumatology clinic during the 2004-2013 period. MATERIAL AND METHOD: Through active search, between January 2004 and December 2013, 152 patients older than 45 years with a diagnosis of lumbar osteoarthritis were identified. RESULTS: Of the total of patients with lumbar osteoarthritis, 81% were female and 19% were male; with ages ranging from 45 to 95 years (mean: 62.24, DS: 10,905). The occupations that were most frequent were: housewives (54%), farmers (10%), drivers (7%), domestic workers (7%), among others. The body postures that were found were: standing frequently (72%), sitting without getting up (17%) and crouching with the back bent (11%). According to the radiological grade of lumbar osteoarthritis, grade 2 or minimal or mild osteoarthritis (48%), grade 3 or moderate osteoarthritis (38%) and grade 4 or severe osteoarthritis (14%) were found. The percentage distribution of radiological degrees of lumbar osteoarthritis by occupational body postures was: crouching with the back bent the frequency of degrees of mild, moderate and severe lumbar osteoarthritis were 3%, 4% and 3% respectively; those with occupational body posture standing frequently 36% had mild lumbar osteoarthritis, 29% moderate osteoarthritis and 7% severe osteoarthritis; sitting without getting up, 9% had lumbar osteoarthritis of a mild radiological grade, 5% had moderate lumbar osteoarthritis, and 3% had severe lumbar osteoarthritis. For the correlation of variables, the Pearson Chi-square statistical test was used, using a significance level of 5% (p value <0.05), obtaining a value of p = 0.150. CONCLUSION: Occupational body posture is not related to the radiological grade of lumbar osteoarthritis in adult patients over 45 years of age with lumbar osteoarthritis. The occupational body posture found most frequently in patients over 45 years of age with lumbar osteoarthritis is standing frequently on foot. The radiological grade of lumbar osteoarthritis most frequently found is grade 2 or minimal or mild osteoarthritis